PENGARUH PEMBERIAN KOMPOS AMPAS TEBU DAN NPK 16:16:16 TERHADAP PERTUMBUHAN SERTA PRODUKSI BUNCIS (Phaseolus vulgaris L.) - Rian Juniarto; Maizar; Raisa Baharuddin (DINAMIKA PERTANIAN, 2018)
ABSTRACT The purpose of this study was to determine the effect of the interaction of bagasse compost and NPK 16:16:16 on the growth and production of green beans. This research uses a factorial completely randomized design (RAL) consisting of 2 factors. The first factor of bagasse compost (A) consists of 4 levels, namely: 0, 600, 1200, 1800 g / plot. The second factor NPK 16:16:16 (N) consists of 4 levels, namely: 0, 16, 24, 32 g / plot. Each treatment consisted of 3 replications so that the total was 48 experimental units. The parameters observed were stem length, flowering age, harvest age, number of pods per plant, pod weight per plant, pod weight per plot, pod length per pod, number of remaining pods. Data were analyzed statistically and continued with a BNJ follow-up test of a 5% level. The results showed that the interaction of bagasse compost and NPK 16:16:16 significantly affected pod weight per plant, pod weight per plot, number of pods per plant, pod length per pod, and number of remaining pods. The best treatment of bagasse compost at a dose of 1200 g / plot and NPK 16:16:16 24 g / plot (A2N2). The main effect of the bagasse compost was evident in all observational parameters. The best treatment is 1200 g / plot (A2). The main effect of the 16:16:16 NPK dose is evident in all observational parameters. The best treatment dose is 24 g / per plot (N2). Keywords: Bagasse compost, NPK, Green Beans